(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article reconstructs elements of the elaboration of the novel Mar azul, by the same author, as of the notion of “ignorant literature” in a path that involves the reflections of Jacques Rancière and Rosalind Krauss, among others, in order to resume a discussion on the question of trans- mission in the literature. In particular, is interested in the possibility of thinking the nonspecific form of literature in confrontation with meaninglessness.The author argues that it is worth recalling a discussion on transmission in literatu- re and its possible relationship with a “lack of wisdom”. In that vein, she wonders if it is possible an “ignorant” place for literature, in the sense that gives Rancière, as an aban- donment of the privilege of a pedagogical overview, without discarding the idea that a text conveys a knowledge and not only a commodity with the signing of an author